OLDER DRIVERS’ ACCEPTANCE OF LONGITUDINAL AND LATERAL VEHICLE WARNING SYSTEMS - Souders, D (Innov Aging, 2018)
Advanced Driver Assistance Systems (ADAS) are rapidly being introduced into new vehicles with each new model year, and their incorporation into the driving task stands to benefit drivers of all ages. However, evidence from studies with largely younger samples suggests that there might be attentional issues that arise when dealing with the alerts from both longitudinal (Forward Collision Warning; FCW) and lateral (Lane Departure Warning; LDW) warning systems that might lead to diminished safety benefits and/or negative effects on system acceptance. In this study, older drivers (N = 128) were randomly assigned to experience one of four system combinations over a ~25-minute drive in a driving simulator: no FCW or LDW, FCW-only, LDW-only, or both FCW and LDW. Participants completed a system acceptance scale before and after experience with their system to gauge their attitudes. Participants’ usefulness and satisfaction scores were similarly positive before and after using their assigned system(s), leading to a lack of significant results between the different conditions on pre- and post-drive difference scores. Regression analyses assessing possible predictors of post-drive usefulness and satisfaction ratings found that female gender was a significant predictor of more positive post-drive usefulness ratings of FCW systems. These findings show that older drivers’ attitudes towards FCW and LDW systems are largely positive and do not differ when these systems are used in tandem, and that older female drivers find FCW systems to be useful after experiencing them on a short, simulated drive.